Where Have All the Experts Gone? An Exploration of Deliberative Pedagogy in Library Instruction - Hernandez Linares, Rosalinda (Université d'Ottawa | University of Ottawa, 2018)
This presentation explores the implications of deliberative pedagogy for libraries, which are imagined as bastions of expertise. As an approach that encourages students to arrive at decisions about socially complex, or ‘wicked problems’ through high-impact meaning-making processes, it necessarily considers authentic, productive dialogues supported by equitable, inclusive environments.